Bridging and Bonding Social Capital: which type is good for economic growth? - Sjoerd Beugelsdijk; Sjak Smulders (European Regional Science Association (ERSA), 2003)
In this paper we develop a model of growth and social capital, and test it using data from the European Value Survey (EVS). Following Putnam's distinction between bonding and bridging social capital, we model social capital as participation in two types of social networks: first, closed networks of family and friends, and, second, open networks that bridge different communities. Agents have a preference for social interaction, which they trade off against material well-being. Participation in both social networks is time-consuming and comes at the cost of participation in the formal economic sphere and working time. Through this channel, higher levels of social capital may crowd out economic growth. In addition, participation in intercommunity networks reduces incentives for rent seeking and cheating. Through this channel, higher level of bridging social capital may enhance economic growth. Testing the model, we find that regional differences in materialistic attitudes and the value attached to family life significantly reduce the participation in open networks and that this in turn reduces regional output growth in Europe.
Keywords: 330